Congenital Infection Influence on Early Brain Development Through the Gut-Brain Axis - Kirschen, Gregory W.; Panda, Snigdha; Burd, Irina (Frontiers in Neuroscience, 2022)
The mechanisms by which various pathogens cause congenital infections have been studied extensively, aiding in the understanding of the detrimental effects these infections can have on fetal/neonatal neurological development. Recent studies have focused on the gut-brain axis as pivotal in neurodevelopment, with congenital infections causing substantial disruptions. There remains controversy surrounding the purported sterility of the placenta as well as concerns regarding the effects of exposure to antibiotics used during pregnancy on neonatal microbiome development and how early exposure to microbes or antibiotics can shape the gut-brain axis. Long-term neurodevelopmental consequences, such as autism spectrum disorder, attention deficit hyperactivity disorder, and cerebral palsy, may be attributable, in part, to early life infection and changes in the immature gut microbiome. The goal of this review is thus to critically evaluate the current evidence related to early life infection affecting neurodevelopment through the gut-brain axis.